Valve-setting and measurement of the power of a 10 H.P. simple engine - Webster, Edwin H. (My University, 1896)
Introduction: The economic use of steam is of first importance to every user of the steam engine. It makes considerable difference in the profit and loss account if a plant is consuming a half or two thirds more coal than it should, because of an incorrect setting of the valves or of some defect in the design of the engine.
Citation: Webster, Edwin H. Valve-setting and measurement of the power of a 10 H.P. simple engine. Senior thesis, Kansas State Agricultural College, 1896.
Morse Department of Special Collections
Keywords: Steam; Steam engine; Coal; Theses; Manuscripts (documents)